2019
DOI: 10.1088/1742-6596/1402/5/055022
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacity of Dillenia sp. leaf extract against DPPH (1,1-Diphenyl-2picryl Hidrazil) radical

Abstract: Some plants have capacity as exogenous antioxidant. Simpor (Dillenia sp.) is plant of the Dilleniaceae family which may have the property of antioxidant. The purpose of this study was to measure the antioxidant capacity of the 96% ethanolic simpor leaf extract. Factorial design was applied with 2x3 factors of maseration time (24 and 48 hours) and concentration series of (10, 15, 20%). Normality was done by Kolmogorov-Smirnov and homogeneity by Levine. Data was analysed by ANOVA (ᾳ = 0.05). Post Hoc was analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The result showed that the ethanol extract of D. serrata leaves had better antioxidant activity than other extracts with a strong level of antioxidant activity. This is in accordance with what was stated by Rahayu, et al (2019), most of the flavonoids and phenols were found in the leaves and have the potential as a source of antioxidants, and are also supported by a study from Sabandar, et al (2017), quercetin compounds are found in the leaves of all types of Dillenia sp. Quercetin is a type of flavonoid antioxidant compound contained in plant foods.…”
Section: Discussionsupporting
confidence: 92%
“…The result showed that the ethanol extract of D. serrata leaves had better antioxidant activity than other extracts with a strong level of antioxidant activity. This is in accordance with what was stated by Rahayu, et al (2019), most of the flavonoids and phenols were found in the leaves and have the potential as a source of antioxidants, and are also supported by a study from Sabandar, et al (2017), quercetin compounds are found in the leaves of all types of Dillenia sp. Quercetin is a type of flavonoid antioxidant compound contained in plant foods.…”
Section: Discussionsupporting
confidence: 92%
“…In comparison, at the lowest concentration of 6.25 ppm, the percentage inhibition was 71.461%, radical inhibitory activity was characterized by increasing sample concentration, and the high concentration of D. excelsa leaf methanol extract, which is 100 ppm, indicates that the content of active antioxidant compounds is more so that the ability to inhibit free radicals will increase. Ethanol extract of D. indica has an inhibition percentage of 97.10±0.01% (Saha et al 2009;Rahayu et al 2019). Ethanolic extract of D. bracteata leaves inhibited 74% with DPPH (Shama et al 2019).…”
Section: Antioxidant Activity Dpph Methods (22-diphenyl-1-picrylhydra...mentioning
confidence: 96%
“…The solution of D. excelsa leaf methanol extract was prepared by weighing 5 mg and diluting with 10 mL of ethanol so that a concentration of 500 µg/mL was formed; variations in concentration were made, namely 200, 100, 50, 25, 12.5, and 6.25 ppm, each concentration was pipetted. 33 µL, added 467 µL of ethanol and 500 mL of 27% DPPH solution, incubated for 20 minutes in a dark room, and measured absorbance using a UV-Vis spectrophotometer with a wavelength of 517 nm (Rahayu et al 2019) The percentage of antioxidant activity was calculated using the following equation:…”
Section: Determination Of the Antioxidant Activity Of Dillenia Excels...mentioning
confidence: 99%
See 2 more Smart Citations